2022
DOI: 10.1021/acs.jpclett.2c03210
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Insight into O2/N2 Permeation Behavior through an Ionomer Film in Cathode Catalyst Layers of Polymer Electrolyte Membrane Fuel Cells

Abstract: It is crucial to clarify the permeation behavior of O 2 through the ionomer film for enhancing local O 2 transport in cathodes of fuel cells. However, all existing studies mainly deal with pure O 2 rather than air. Herein, the permeation behavior of the O 2 /N 2 mixture through the ionomer film has been well explored in view of molecular bond length variations by molecular dynamics simulations. The bond lengths for O 2 and N 2 are shortened under a low hydration level when permeating through a dense layer with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…22,38 It is worth emphasizing that the modied DREIDING force elds employed in this study have undergone extensive verication and are widely accepted and utilized in the eld of PEMFCs. 16,22,39 We performed the MD simulations based on the modied DREIDING force elds, and the details of model validation are explained in the ESI. †…”
Section: Parameters and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…22,38 It is worth emphasizing that the modied DREIDING force elds employed in this study have undergone extensive verication and are widely accepted and utilized in the eld of PEMFCs. 16,22,39 We performed the MD simulations based on the modied DREIDING force elds, and the details of model validation are explained in the ESI. †…”
Section: Parameters and Proceduresmentioning
confidence: 99%
“…This speculation is also supported by the experimental results that the oxygen diffusivity in water is four times higher than that of the hydrophobic PTFE, 6 as well as the theoretical simulations that the water, hydronium ions, and oxygen molecules typically diffuse through water clusters. 13 In contrast, there is also increasing evidence that oxygen has a greater affinity for the hydrophobic phases of the ionomer, [14][15][16][17] thus tending to diffuse via the hydrophobic or interfacial regions. Zhang et al 16 revealed that oxygen prefers to diffuse through the hydrophobic and interfacial regions since oxygen is energetically unstable in hydrophilic water domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well acknowledged that local oxygen transport resistance originates from the transport process through the ionomer film that covered the Pt surfaces, where the ionomer film mainly consists of perfluorosulfonic acid polymers and possesses densely aggregated structures that in turn limit oxygen transport. , Accordingly, great efforts have been made to explore the intrinsic mechanism of local oxygen transport through the ionomer film. On the basis of experimental results, Kudo et al proposed a solution-diffusion model, which indicates that local oxygen transport includes three steps, i.e., oxygen absorbing on the ionomer surface, diffusing within the ionomer film, and adsorbing on the Pt surface, among which the largest transport resistance is observed at the Pt/ionomer interface. , In addition, molecular dynamics (MD) simulations have also provided new insights from nanoscale perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous applications of electrocatalysis in technological chemical processes such as organic synthesis, sensors, fuel cells, Li-ion batteries, nitrogen reduction reactions (NRR), CO 2 reduction, etc. Among them, the most promising, environmentally friendly, and environmentally sustainable method of producing hydrogen and oxygen is known as the electrocatalytic water-splitting reaction. , Water is electrolyzed using two half-cell processes, the HER and the OER, which take place at the cathode and anode, respectively .…”
mentioning
confidence: 99%